Moderate Grazing Increases Water Use Efficiency for Environmental Health in Alpine Meadows of the Tibetan Plateau - Wang, Yunying; Pei, Weiwei; Cao, Guangmin; Guo, Xiaowei; Zhou, Huakun; Du, Yangong (Frontiers in Ecology and Evolution, 2021)
Water use efficiency is an important indicator of drought tolerance in plants. The response of the water use efficiency to different grazing intensities and adaptive mechanisms in alpine meadows remains unclear. To understand the changes in water use in alpine meadow ecosystems under different grazing gradients, grazing systems have to be optimized, and severely receding grasslands should be effectively restored. This study analyzed the response of water use efficiency of plant dominant species, coexisting species, and functional group-level plants to grazing intensity using the δ13C index in an alpine meadow. We found that grazing increased the leaf carbon isotope composition in plants (δ13C) of Gramineae by 3.37% and grazing at a moderate level significantly increased it by 4.84% (P < 0.05). In addition, an increase in δ13C was observed in the functional groups of Cyperaceae (3.45%), Leguminosae (0.81%), and Forb (1.40%). However, some dominant species and coexisting species showed the highest δ13C values under moderate grazing. These results indicate that moderate grazing may significantly improve the water use efficiency of species in alpine meadows. The path analysis showed that water use efficiency was negatively correlated with evapotranspiration (P < 0.05), soil water content, soil organic carbon, and soil bulk density. Nevertheless, there was a positive correlation between water use efficiency and the available nitrogen. This study concluded that moderate grazing could improve the efficiency of grassland water use to a certain extent. Additionally, soil evapotranspiration was the main driving factor affecting the water use efficiency of alpine meadows.